Method for testing corrosion resistance of automobile coating

Through a multi-stage cycle test method, combined with neutral salt spray, artificial bird droppings, temperature and humidity alternation and high-pressure flushing test, the problem of insufficient test under single conditions in the existing technology is solved, and the automotive coating is realized under complex environments More accurate evaluations improve the corrosion resistance of the coating and design accuracy.

CN119178716APending Publication Date: 2024-12-24CHINA FAW CO LTD

Patent Information

Application Number
CN202411280409.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing corrosion resistance test methods for automotive coatings. The neutral salt spray test under a single condition cannot fully simulate the complex service environment, and cannot reflect the coupling effect of automotive coatings under multiple corrosive media, resulting in insufficient design and development.

Method used

Multi-stage cycle test methods are adopted, including neutral salt spray test, artificial bird dropping corrosion test, temperature and humidity alternation test and high-pressure flushing test, to simulate various corrosion conditions in outdoor driving and parking scenarios, and to evaluate the corrosion resistance of the coating. sex.

Benefits of technology

This method can more accurately evaluate the corrosion resistance of automotive coatings in complex environments, provide a design basis closer to actual use scenarios, and enhance the corrosion resistance and service life of the coatings.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an automobile coating corrosion resistance test method. The automobile coating corrosion resistance test method comprises the following steps: (1) performing test pretreatment on a tested sample; (2) corrosion resistance tests are carried out for 10-25 cycles, each cycle comprises a phase A test, a phase B test, a phase C test and a phase D test, the phase A is a neutral salt spray test, the phase B is an artificial bird droppings corrosion test, the phase C is a temperature and humidity alternating test, and the phase D is a high-pressure flushing test; and (3) after the cyclic test is finished, testing the corrosion resistance index of the coating. According to the method, outdoor driving and parking scenes can be better simulated, the coupling effect of various conditions and corrosive media on coating corrosion is reflected, and a more accurate theoretical basis is provided for design and development of automobile coating products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coating corrosion testing, and in particular to a method for testing the corrosion resistance of automobile coatings. Background Art

[0002] Automobile coating is an important part of automobiles, and it undertakes two major missions: decorative function and protective function. As one of the main means of daily travel, automobiles will be corroded by various media in the atmosphere, such as moisture, oxygen, industrial waste gas, carbon dioxide, etc. during service. The coating can prevent the chemical reaction and / or electrochemical reaction between the automobile surface and the surrounding media to a certain extent, and prevent or delay the damage of the surrounding media to the automobile. At present, for the corrosion resistance of automobile coatings, the industry usually uses the neutral salt spray test to test the corrosion resistance according to the method specified in "GB T 1771-2007 Determination of the resistance of paints and varnishes to neutral salt spray". With the in-depth study of the types and mechanisms of automobile corrosion, people have a deeper demand for the protection of coatings. The neutral salt spray test, a corrosion test under a single condition, is not close enough to the actual use scenario, and does not reflect the coupling effect of the complex service environment of the automobile on the coating life, which is not conducive to the design and development of automobile coatings.

[0003] Therefore, the current test methods for corrosion resistance of automotive coatings still need to be improved. Summary of the invention

[0004] The present invention aims to alleviate or solve at least one of the above-mentioned problems to at least some extent.

[0005] In one aspect of the present invention, the present invention proposes a method for testing the corrosion resistance of automobile coatings. In some embodiments of the present invention, the method for testing the corrosion resistance of automobile coatings comprises the following steps: (1) performing pre-test treatment on the test sample; (2) performing 10-25 cycles of corrosion resistance test, each cycle including sequentially performing tests in stages A, B, C and D, wherein stage A is a neutral salt spray test, stage B is an artificial bird droppings corrosion test, stage C is a temperature and humidity alternation test, and stage D is a high-pressure flushing test; (3) after the cycle test, testing the corrosion resistance index of the coating. This method can better simulate outdoor driving and parking scenes, reflecting the coupling effects of various conditions and corrosive media on coating corrosion, and providing a more accurate theoretical basis for the design and development of automobile coating products.

[0006] In some embodiments of the present invention, the corrosion resistance index includes at least one of whether the sample under test is rusted, the rust area, the number of cycles when rust occurs, and the gloss change before and after the test. During the test, different corrosion resistance indicators can be selected for evaluation according to customer needs.

[0007] In some embodiments of the present invention, the pre-test treatment includes: placing the test sample in an environment of 21° C.-25° C. and 45% RH-55% RH for 16 h-24 h.

[0008] In some embodiments of the present invention, the neutral salt spray test in stage A includes: placing the test sample in a salt spray chamber, with the test surface facing upward and maintaining an angle with the vertical direction in the range of 15°-25°, and conducting a neutral salt spray test for 12h-48h. The salt solution used is a sodium chloride solution with a concentration of 45g / L-55g / L, a pH value between 6.5-7.2, and a test temperature of 33°C-37°C.

[0009] In some embodiments of the present invention, the artificial guano corrosion test in stage B includes: rinsing and drying the surface of the test sample, applying an artificial guano solution on the test surface, and then placing the test sample in a drying oven at 40° C. to 60° C. for 0.8 h to 1.2 h.

[0010] In some embodiments of the present invention, 0.1 mL to 0.3 mL of the artificial guano solution is applied to the test surface.

[0011] In some embodiments of the present invention, the artificial guano solution uses an albumin aqueous solution with a mass concentration of 2.5%-3.5%, or the artificial guano solution uses a pancreatic enzyme suspension with a mass concentration of 4.5%-5.5%. Thus, outdoor driving and parking scenes can be better simulated.

[0012] In some embodiments of the present invention, the temperature and humidity alternation test in stage C includes: placing the test sample in a high and low temperature humidity test chamber for a temperature and humidity alternation test, the test chamber is heated from room temperature to 78°C-82°C over 0.8h-1.2h, and maintained at 78°C-82°C, 75%RH-85%RH for 3.5h-4.5h, then cooled to -42°C~-38°C over 1.5h-2.5h and maintained for 3.5h-4.5h, then the test sample is taken out and adjusted in an environment of 21°C-25°C, 45%RH-55%RH for 0.8h-1.2h.

[0013] In some embodiments of the present invention, the high-pressure flushing test in stage D includes: using a high-pressure cleaning machine to perform high-pressure flushing on the sample, the temperature of the flushing medium is 68° C.-72° C., the flushing pressure is 8.5 MPa-9.5 MPa, and the flushing time is 10s-20s.

[0014] In some embodiments of the present invention, pre-test treatment includes: placing the test sample in an environment of 21°C-25°C, 45%RH-55%RH for 16h-24h, making a 10mm-30mm long scratch on the surface of the test sample, and the scratch penetrates the coating of the test sample directly to the substrate of the test sample.

[0015] In some embodiments of the present invention, the corrosion resistance index includes the corrosion expansion distance of the tested sample. DETAILED DESCRIPTION

[0016] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0017] In one aspect of the present invention, the present invention provides a method for testing the corrosion resistance of an automobile coating. In some embodiments of the present invention, the method for testing the corrosion resistance of an automobile coating may include the following steps:

[0018] (1) Carry out pre-test treatment on the test samples.

[0019] In some embodiments of the present invention, pre-test treatment may include the following steps: placing the test sample in an environment of 21°C-25°C, 45%RH-55%RH and adjusting it for 16h-24h. For example, the test sample can be placed in an environment of 21°C, 22°C, 23°C, 24°C or 25°C and 45%RH, 48%RH, 50%RH, 52%RH or 55%RH and adjusted for 16h, 18h, 20h, 22h or 24h.

[0020] In other embodiments of the present invention, the pre-test treatment may include the following steps: placing the test sample in an environment of 21°C-25°C, 45%RH-55%RH for 16h-24h, and making a scratch of 10mm-30mm in length on the surface of the test sample, and the scratch penetrates the coating of the test sample directly to the substrate of the test sample. In some embodiments, the length of the scratch may be 10mm, 15mm, 20mm, 25mm or 30mm, and the scratch of the above length is convenient for subsequent observation and evaluation. In some specific embodiments of the present invention, if there is a test requirement, a scratch tool with a hard tip can be used to make a scratch on the surface of the test sample. The scratch needs to penetrate the coating directly to the substrate (base material) of the test sample, and the corrosion resistance of the coating can be judged later by the corrosion expansion width (corrosion expansion distance) of the test sample.

[0021] (2) Carry out 10-25 cycles of corrosion resistance test, each cycle includes the tests of stage A, stage B, stage C and stage D in sequence, among which stage A is a neutral salt spray test, stage B is an artificial bird droppings corrosion test, stage C is a temperature and humidity alternation test, and stage D is a high-pressure flushing test.

[0022] After the pre-test treatment, the test sample is subjected to a corrosion resistance test for 10-25 cycles. In some embodiments of the present invention, a corrosion resistance test for 10, 15, 20 or 25 cycles may be performed.

[0023] In some embodiments of the present invention, the neutral salt spray test in phase A may include the following steps: placing the test sample in a salt spray chamber, with the test surface (coating) facing upward and maintaining an angle with the vertical direction in the range of 15°-25°, and conducting a neutral salt spray test for 12h-48h, using a salt solution of 45g / L-55g / L sodium chloride solution, a pH value between 6.5-7.2, and a test temperature of 33°C-37°C. In some embodiments, the test surface (coating) of the test sample faces upward, and the angle between the test surface and the vertical direction may be 15°, 18°, 20°, 23°, or 25°. In some embodiments, the neutral salt spray test may be conducted for 12 hours, 24 hours, 36 hours or 48 hours, the salt solution used may be a sodium chloride solution with a concentration of 45 g / L, 48 g / L, 50 g / L, 52 g / L or 55 g / L, and the test temperature may be 33° C., 34° C., 35° C., 36° C. or 37° C. For specific equipment conditions and test methods, reference may be made to GB T 1771-2007 Determination of neutral salt spray resistance of paints and varnishes or GB / T 10125-2021 Salt spray test for corrosion test in artificial atmosphere.

[0024] In some embodiments of the present invention, the artificial bird droppings corrosion test in phase B may include the following steps: rinsing and drying the surface of the test sample, applying an artificial bird droppings solution on the test surface, and then placing the test sample in a drying oven at 40°C-60°C for 0.8h-1.2h. In this way, the scene of bird droppings falling on the car during outdoor driving or parking can be simulated, so that the test is closer to the actual use scenario.

[0025] In some embodiments of the present invention, clean water may be used to rinse the sample surface, and the clean water may be pure water obtained after filtration.

[0026] In some embodiments of the present invention, 0.1 mL-0.3 mL of the artificial guano solution may be applied to the test surface. For example, 0.1 mL, 0.15 mL, 0.2 mL, 0.25 mL or 0.3 mL of the artificial guano solution may be applied to the test surface.

[0027] In some embodiments of the present invention, the artificial guano solution can be an albumin aqueous solution with a mass concentration of 2.5%-3.5%. For example, the artificial guano solution can be an albumin aqueous solution with a mass concentration of 2.5%, 2.8%, 3%, 3.2% or 3.5%. This type of artificial guano solution can be used to simulate the corrosion effect of protein on the coating.

[0028] In some embodiments of the present invention, the artificial guano solution can be a pancreatic enzyme suspension with a mass concentration of 4.5%-5.5%. For example, the artificial guano solution can be a pancreatic enzyme suspension with a mass concentration of 4.5%, 4.7%, 5%, 5.3% or 5.5%. The dispersant in the pancreatic enzyme suspension is water. This type of artificial guano solution can be used to simulate the corrosion effect of pancreatic enzyme on the coating. If an artificial guano solution with pancreatic enzyme components is used for testing, a lower drying temperature can be selected to avoid inactivation of pancreatic enzyme.

[0029] Artificial bird droppings solution is used to test the corrosion resistance of automobile coatings to bird droppings. During the test, the changes of the automobile under the action of artificial bird droppings (for example, gloss change, whether there is rust, rust area, etc.) can be recorded to evaluate the corrosion resistance of the coating.

[0030] In some embodiments of the present invention, the temperature and humidity alternation test in stage C may include the following steps: placing the test sample in a high and low temperature humidity test chamber for a temperature and humidity alternation test, the test chamber is heated from room temperature to 78°C-82°C over 0.8h-1.2h, and maintained at 78°C-82°C, 75%RH-85%RH for 3.5h-4.5h, then cooled to -42°C~-38°C over 1.5h-2.5h and maintained for 3.5h-4.5h, then the test sample is taken out and adjusted in an environment of 21°C-25°C, 45%RH-55%RH for 0.8h-1.2h.

[0031] In some embodiments of the present invention, the test sample can be placed in a high and low temperature humidity test chamber for temperature and humidity alternation test, the test chamber is heated from room temperature to 78°C, 79°C, 80°C, 81°C or 82°C for 0.8h, 0.9h, 1h, 1.1h or 1.2h, and maintained at 78°C-82°C, 75%RH, 78%RH, 80%RH, 82%RH or 85%RH for 3.5h, 3.7h, 4h, 4.2h or 4.5h, and then heated for 1.5h. The temperature is decreased to -42°C, -41°C, -40°C, -39°C or -38°C for 3.5h, 3.8h, 4h, 4.3h or 4.5h, and then the test samples are taken out and conditioned at 21°C, 22°C, 23°C, 24°C or 25°C and 45%RH, 47%RH, 50%RH, 52%RH or 55%RH for 0.8h, 0.9h, 1h, 1.1h or 1.2h.

[0032] The temperature and humidity alternating test can simulate the temperature and humidity conditions in the actual use environment, evaluate the performance of the coating during actual use, accelerate the aging of the coating, and evaluate whether the coating is long-term durable in a shorter period of time.

[0033] In some embodiments of the present invention, the conditions of the temperature and humidity alternating test can be adjusted according to needs. For example, the low temperature section can be eliminated and high temperature and high humidity conditions can be maintained throughout the whole process, etc., which will not be listed one by one in this article.

[0034] In some embodiments of the present invention, the high-pressure washing test in stage D may include the following steps: using a high-pressure cleaning machine to wash the test sample under high pressure, the temperature of the washing medium may be 68°C-72°C, the washing pressure may be 8.5MPa-9.5MPa, and the washing time may be 10s-20s. Thus, the above-mentioned high-pressure washing test can simulate the scene of washing a car.

[0035] In some embodiments of the present invention, a high-pressure cleaner can be used to perform high-pressure washing on the test sample. The temperature of the washing medium can be 68°C, 69°C, 70°C, 71°C or 72°C, the washing pressure can be 8.5MPa, 8.8MPa, 9MPa, 9.2MPa or 9.5MPa, and the washing time can be 10s, 12s, 15s, 17s or 20s.

[0036] In some embodiments of the present invention, clean water may be used to perform high-pressure washing on the test sample.

[0037] In other embodiments of the present invention, a 5% car cleaning agent solution (a mixture of car cleaning agent and water, the mass of the car cleaning agent accounts for 5% of the total mass of the solution) can be used as the flushing medium. The specific components of the car cleaning agent are not particularly limited in the present invention, and those skilled in the art can select a commonly used car cleaning agent according to actual conditions.

[0038] High-pressure washing can simulate the water impact during the car washing process, which can help evaluate the performance of automotive coatings during actual use. Through high-pressure washing tests, the performance differences of different coatings can be compared and the composition and performance of the coatings can be optimized according to customer needs.

[0039] (3) After the cycle test, the corrosion resistance index of the coating is tested.

[0040] In some embodiments of the present invention, the corrosion resistance index may include at least one of whether the sample under test is rusted, the area of ​​rust, the number of cycles when rust occurs, and the gloss change before and after the test. The corrosion resistance index can be selected according to customer needs, and may include one of whether rust occurs, the area of ​​rust, the number of cycles when rust occurs, and the gloss change before and after the test, or may include multiple of the above indicators. If the gloss change needs to be examined, the gloss test can be performed in this step and the original value can be recorded.

[0041] In some embodiments of the present invention, the modified area and the number of cycles when rust occurs can be used as corrosion resistance indicators. In other embodiments of the present invention, whether rust occurs and the gloss change before and after the test can be used as corrosion resistance indicators.

[0042] In some embodiments of the present invention, the pre-test treatment includes making a scratch of 10mm-30mm in length on the surface of the test sample, and the scratch penetrates the coating of the test sample directly to the substrate of the test sample, and the corrosion resistance index may include the corrosion expansion distance of the test sample. In some embodiments, the corrosion resistance index may include the maximum corrosion expansion width of the test sample. It should be noted that the maximum corrosion expansion width of the test sample refers to the coating on both sides of the scratch that may fall off after multiple cycles of testing. The maximum width of the coating that falls off on one side of the scratch in the direction perpendicular to the scratch is the maximum corrosion expansion width of the test sample.

[0043] In the present invention, on the basis of the neutral salt spray test, three tests are added: artificial bird droppings resistance test, temperature and humidity alternation test, and high-pressure washing test. The method provided by the present invention can better simulate outdoor driving and parking scenes, reflecting the coupling effect of various conditions and corrosive media on coating corrosion, and providing a more accurate theoretical basis for the design and development of automotive coating products.

[0044] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the materials and equipment used are all commercially available. If in the following examples, specific processing conditions and processing methods are not clearly described, then conditions and methods known in the art can be used to process.

[0045] Example 1

[0046] A zinc-aluminum coated product was selected as a test sample, and the test sample was placed in an environment of 23°C and 50% RH for 24 hours. After that, a corrosion resistance test including four stages AD and a total of 20 cycles was directly carried out without any other treatment.

[0047] Phase A: Place the test sample in a salt spray chamber, with the test surface (coating) facing upward and maintaining an angle of 25° with the vertical direction, and conduct a 36-hour neutral salt spray test. The selected salt solution is a sodium chloride solution with a concentration of 50g / L, a solution pH of 6.9, and a test temperature of 35°C.

[0048] Phase B: Rinse the surface of the test sample with clean water and wipe it dry, apply 0.2 mL of artificial guano solution on the test surface. The artificial guano solution uses a 3% albumin aqueous solution, and then place the test sample in a drying oven at 60°C and dry it for 1 hour.

[0049] Phase C: Place the test samples in a high and low temperature humidity test chamber for temperature and humidity alternation test. The test chamber is heated from room temperature to 80°C over 1 hour and maintained at 80°C, 80% RH for 4 hours. Then, it is dropped to -40°C over 2 hours and maintained for 4 hours. The test samples are then taken out and adjusted at 21°C, 52% RH for 1 hour, for a total of 12 hours.

[0050] Phase D: Use a high-pressure cleaner to perform high-pressure washing on the test samples. The temperature of the washing medium is 70.7℃, the pressure is 8.92MPa, the washing medium is clean water, and the washing time is 10s.

[0051] After the cycle is completed, observe the surface corrosion status of the test sample. If there is corrosion, roughly estimate the corrosion area.

[0052] Test results: After 20 cycles of testing, matrix corrosion products appeared on the tested samples, and the rust area was between 0.5% and 1%.

[0053] Example 2

[0054] An automobile paint coating product was selected as the test sample. The test sample was placed in an environment of 23°C and 50% RH for 24 hours. A scratch about 20 mm long was scratched on the surface of the test sample to reach the substrate. Then, a corrosion resistance test totaling 15 cycles including four stages AD was carried out.

[0055] Phase A: Place the test sample in a salt spray chamber, with the test surface (coating) facing upward and maintaining an angle of 25° with the vertical direction, and conduct a 24-hour neutral salt spray test. The selected salt solution is a sodium chloride solution with a concentration of 50g / L, a solution pH of 6.7, and a test temperature of 35°C.

[0056] Phase B: Rinse the surface of the test sample with clean water and wipe it dry, apply 0.3 mL of artificial guano solution on the test surface. The artificial guano solution uses a 5% pancreatic enzyme suspension, and the dispersant in the pancreatic enzyme suspension is water. Then place the test sample in a drying oven at 40°C and dry it for 1.2 hours.

[0057] Phase C: Place the test samples in a high and low temperature humidity test chamber for temperature and humidity alternation test. The test chamber is heated from room temperature to 80°C over 1 hour and maintained at 80°C, 80% RH for 4 hours. Then, it is dropped to -40°C over 2 hours and maintained for 4 hours. The test samples are then taken out and adjusted at 21°C, 52% RH for 1 hour, for a total of 12 hours.

[0058] Phase D: Use a high-pressure cleaner to perform high-pressure washing on the test samples. The temperature of the washing medium is 70.7°C, the pressure is 9.12MPa, the washing medium is a 5% concentration of automotive cleaning agent solution, and the washing time is 20s.

[0059] After the cycle is completed, measure the distance the scratch expands to both sides and take the maximum value as the test result.

[0060] Test results: After 15 cycles of testing, the maximum corrosion width of the test sample was 1.4 mm.

[0061] Comparative Example 1

[0062] The same zinc-aluminum coated product in Example 1 was selected as the test sample in Comparative Example 1, and the test sample was placed in an environment of 23°C and 50% RH for 24 hours, and then directly subjected to a 720-hour neutral salt spray test without any other treatment. The specific method is: the test sample is placed in a salt spray chamber, with the test surface (coating) facing upward and maintaining an angle of 25° with the vertical direction, and a 720-hour neutral salt spray test is conducted. The selected salt solution is a sodium chloride solution with a concentration of 50 g / L, a solution pH of 6.9, and a test temperature of 35°C.

[0063] After the salt spray test, observe the surface corrosion of the test sample. If there is corrosion, roughly estimate the corrosion area.

[0064] Test results: After 720h of neutral salt spray test, matrix corrosion products appeared on the tested samples, and the rust area was between 0.1% and 0.5%. Compared with the rust area of ​​the tested samples in Example 1, the rust area of ​​the tested samples in Comparative Example 1 was smaller.

[0065] Comparative Example 2

[0066] The same automotive paint coating product in Example 2 was selected as the test sample, and the test sample was placed in an environment of 23°C and 50% RH for 24 hours. A scratch of about 20 mm long reaching the substrate was scratched on the surface of the test sample, and then a 360-hour neutral salt spray test was performed. The specific method is: the test sample is placed in a salt spray chamber, the test surface (coating) is facing upward and the angle with the vertical direction is maintained at 25°, and a 360-hour neutral salt spray test is performed. The selected salt solution is a sodium chloride solution with a concentration of 50g / L, a solution pH value of 6.7, and a test temperature of 35°C.

[0067] After the neutral salt spray test is completed, measure the distance the scratches extend to both sides and take the maximum value as the test result.

[0068] Test results: After 360h of neutral salt spray test, the maximum corrosion width of the tested sample was 0.6mm.

[0069] In the description of this specification, the description with reference to the terms "some embodiments", "other embodiments", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory. In addition, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.

[0070] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for testing the corrosion resistance of automobile coatings, characterized in that: The following steps are involved: (1) Carry out pre-test treatment on the test samples; (2) Conduct 10-25 cycles of corrosion resistance test, each cycle includes the tests of stage A, stage B, stage C and stage D in sequence, where stage A is a neutral salt spray test, stage B is an artificial bird droppings corrosion test, stage C is a temperature and humidity alternation test, and stage D is a high-pressure washing test; (3) After the cycle test, the corrosion resistance index of the coating is tested.

2. The method according to claim 1, characterized in that The corrosion resistance index includes at least one of whether the test sample is rusted, the rust area, the number of cycles when rust occurs, and the gloss change before and after the test.

3. The method according to claim 1, characterized in that: The pre-test treatment includes: placing the test sample in an environment of 21°C-25°C, 45%RH-55%RH for 16h-24h.

4. The method according to claim 1, characterized in that: The neutral salt spray test in Phase A includes: placing the test sample in a salt spray chamber with the test surface facing upward and maintaining an angle of 15°-25° with the vertical direction, and conducting a neutral salt spray test for 12h-48h. The salt solution used is a sodium chloride solution with a concentration of 45g / L-55g / L, a pH value between 6.5-7.2, and a test temperature of 33℃-37℃.

5. The method according to claim 1, characterized in that: The artificial guano corrosion test in phase B includes: rinsing and drying the surface of the test sample, applying an artificial guano solution on the test surface, and then placing the test sample in a drying oven at 40°C-60°C to dry for 0.8h-1.2h; Optionally, 0.1 mL to 0.3 mL of artificial guano solution is applied to the test surface.

6. The method according to claim 5, characterized in that The artificial guano solution adopts an albumin aqueous solution with a mass concentration of 2.5%-3.5%, or the artificial guano solution adopts a pancreatic enzyme suspension with a mass concentration of 4.5%-5.5%.

7. The method according to claim 1, characterized in that The temperature and humidity alternation test in Phase C includes: placing the test samples in a high and low temperature humidity test chamber for temperature and humidity alternation test. The test chamber is heated from room temperature to 78℃-82℃ over 0.8h-1.2h, and maintained at 78℃-82℃, 75%RH-85%RH for 3.5h-4.5h, then dropped to -42℃~-38℃ over 1.5h-2.5h and maintained for 3.5h-4.5h. The test samples are then taken out and adjusted in an environment of 21℃-25℃, 45%RH-55%RH for 0.8h-1.2h.

8. The method according to claim 1, characterized in that: The high-pressure flushing test in stage D includes: using a high-pressure cleaning machine to high-pressure flush the sample, the temperature of the flushing medium is 68℃-72℃, the flushing pressure is 8.5MPa-9.5MPa, and the flushing time is 10s-20s.

9. The method according to any one of claims 1 to 8, characterized in that The pre-test treatment includes: placing the test sample in an environment of 21℃-25℃, 45%RH-55%RH for 16h-24h, making a 10mm-30mm long scratch on the surface of the test sample, and the scratch penetrates the coating of the test sample directly to the substrate of the test sample.

10. The method according to claim 9, characterized in that The corrosion resistance index includes the corrosion expansion distance of the tested sample.

Citation Information

Patent Citations

  • Vehicle body testing bin accelerated corrosion testing method

    CN107144524A

  • Low-VOC (volatile organic compound) super-curing repairing varnish and preparation method thereof

    CN108276886A

  • Artificial bird droppings liquid and method for detecting bird droppings resistance of coating

    CN111175220A

  • Evaluation method for corrosion test of automobile radiator

    CN113866081A

  • Automobile paint film corrosion resistance and washing resistance testing device

    CN211318075U

Cited By

  • Automobile washing environment pressure tolerance comprehensive evaluation system and evaluation method

    CN120445668A

  • Salt spray composite test method for slurry treatment and application

    CN121384774A